Web-Based Thrifting Platform for Selling Second-Hand Goods (Your Favorite Shirt) - Setya Putri, Heravi Atha; Ayu Rosanda, Pramaysella Ayu Rosanda; Tri Anggira, Tisa; Zakialdy, Vicky Vidiana (Yayasan Kawanad, 2025)
This study examines the development and implementation of Your Favorite Shirt, a web-based platform designed to modernize thrift shop operations through digital transformation. Many thrift businesses in Indonesia still rely on manual processes or social media, leading to inefficiencies in inventory management, transaction tracking, and reporting. To address these challenges, a prototype-based development method was applied, involving requirement analysis, initial design, prototype construction, user testing, and iterative refinement. The system integrates key features such as multi-role login, product catalogues, transaction management, payment options, and order tracking. Evaluation through functional testing and the PIECES framework demonstrated positive results across performance, efficiency, control, and service dimensions, with an average system response time of under one second. User Acceptance Testing (UAT) with a Likert-scale questionnaire produced a mean score of 1.85, indicating strong user satisfaction. Beyond improving operational efficiency, the platform also supports sustainable fashion practices by curating quality secondhand products and reducing textile waste. However, risk assessment identified several areas requiring improvement, including the absence of a Business Continuity Plan, limited access control mechanisms, and lack of systematic documentation. Future development should focus on integrating social media APIs, implementing product recommendation systems, enhancing layered security, and deploying analytical dashboards to support data-driven decision-making.